Protection Motivation Theory and Contingent Valuation: Perceived Realism, Threat and WTP Estimates for Biodiversity Protection - Riccardo Scarpa; Susanne Menzel (Fondazione Eni Enrico Mattei (FEEM), 2005)
We report on a discrete-choice CV study conducted in Germany to value the WTP for biodiversity protection in less developed countries. To systematically investigate survey realism and subjective threat assessment from the loss of biodiversity described in the scenario the study includes questions to uncover the constructs of Protection Motivation Theory, which is introduced to the CV literature. The patterns of responses to such questions are analysed using an Expectation-Maximization algorithm to derive class membership probabilities. These are found to match the predictions of Protection Motivation Theory and systematically improve the logistic analysis of the WTP responses.
Keywords: Q2; D6; C42; C25; 330; Biodiversity valuation; Protection motivation theory; Latent class analysis; Expectation-Maximization algorithm; Contingent valuation; Biodiversität; Willingness to pay; Deutschland; Diskrete Entscheidung